DIFFERENT LEARNING STRATEGIES PREFERENCE AMONG SENIOR HIGH SCHOOL STUDENTS OF DIFFERENT PROGRAMS - Aning Maudini; Arni Nurhasanah; Euis Rina Mulyani (PROJECT (Professional Journal of English Education), 2018)
In Indonesia, the position of English is as an foreign language. This is studied in formal schools as an important subject but not used for daily communication outside the classrooms. This condition become a big challenge for Indonesian students. They are defiance to employ various strategies to become successful English-language learners. This study was aimed to know the habitually of students' in strategies language learning use among students of different program: natural science and social science. The research design of this study is quantitative approach since it examines tendency and the data was in numerical form. The study was conducted at a Senior High School in Cikalong Kulon- Cianjur. In this study, the subject are 120 students containing of 60 natural science students and 60 social science students. The data was using SILL questionnaire. This questionnaire measures 6 strategies types of strategies language learning  which contains of 50 items. The data was analyzed using Microsoft Excel 2013 to calculate and to know the number and average, the last is rank to find the liability of language learning strategies used by both Social science students and natural science students. The data showing that the liability of types of strategies language learning used by the students are different. Natural science students most oftentimes used Compensation strategies. In contrast, social science students used metacognitive strategy as the most oftentimes used strategy.Keywords:  SILL, Language Learning Strategies, Learning English